Present-Day Stage of Capitalism and Economic Liberalism (Economic and Political Thought, 2013)
According to the authors, the major direct threats that undermine thepresent-day capitalism are the weakness of state institutions and, as a result,defects of market regulations on the one hand, and market deformationsconnected with the loss of appropriate self-regulation of particular markets,especially the financial one, on the other hand. The authors believe that thesubstantial reason of those threats lies in the sphere of the political systemtransformation. With the use of the political doctrines set, in the middle ofwhich there is the economic liberalism based on the philosophic liberalism,the authors point out the consequences of the transformation in the USAafter 1980, followed by Europe and Poland from the very beginning of thetransformation, and other states, to the system called neo-liberalism. In theauthors’ opinions, the best solution for the world would be a re-entry into theliberal system, in which the relations between the state and markets wouldbe of a cooperative character making it possible to achieve synergic effects.